2015
DOI: 10.1039/c5fo00471c
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and antitumor efficacy evaluation of a polysaccharide from Nostoc commune Vauch.

Abstract: Nostoc commune Vauch. has been traditionally used as a healthy food and medicine for centuries especially in China. It has been demonstrated that the polysaccharides isolated from Nostoc commune Vauch. exhibit strong antimicrobial and antioxidant activities. However, little is known about their anticancer activities and the underlying mechanisms of action. Herein, we report the isolation of a polysaccharide from Nostoc commune Vauch. (NVPS), and its physicochemical properties were analyzed. In an attempt to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 41 publications
2
17
0
2
Order By: Relevance
“…In addition to induction of apoptosis, other mechanisms may also be involved in the anti-proliferative effect of Nostoc polysaccharides. For example, a polysaccharide from N. commune is able to suppress proliferation of MCF-7 cells via modulation of endoplasmic reticulum stress, which is known to trigger unfolded protein response and lead to cell death [ 53 ]. Also, a number of studies have shown that the anti-tumor activity of polysaccharides is closely associated with their regulatory effects on immune system [ 54 , 55 ], and, intriguingly, N. commune polysaccharide has been previously shown to activate the complement system [ 2 ], an important part of the immune system acting to enhance the adaptive immune response.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to induction of apoptosis, other mechanisms may also be involved in the anti-proliferative effect of Nostoc polysaccharides. For example, a polysaccharide from N. commune is able to suppress proliferation of MCF-7 cells via modulation of endoplasmic reticulum stress, which is known to trigger unfolded protein response and lead to cell death [ 53 ]. Also, a number of studies have shown that the anti-tumor activity of polysaccharides is closely associated with their regulatory effects on immune system [ 54 , 55 ], and, intriguingly, N. commune polysaccharide has been previously shown to activate the complement system [ 2 ], an important part of the immune system acting to enhance the adaptive immune response.…”
Section: Resultsmentioning
confidence: 99%
“…Some chlorophytes and most cyanophytes have a high production of these polysaccharides and mucilage, as they are components of the cell wall (Ghosh, 2018). Recent research uncovered their many possible applications not only in agriculture but also in biomedicine due to their antibacterial, antiviral, antifungal, and anticoagulant activity (Guo et al, 2015;Berri et al, 2016;Faggio et al, 2016).…”
Section: Biofertilization With Chlorophyta and Cyanophyta As An Altermentioning
confidence: 99%
“…Полисахарид из Nostoc commune Vauch. может запускать внешние, внутренние и эндоплазматические ретикулумные стрессы (ERS)опосредованных апоптотических сигнальных путей и может использоваться в качестве нового перспективного источника природных противоопухолевых агентов (Guo, 2015). Апоптоз является важным процессом для предотвращения рака, и раковые клетки избегают этих процессов, поэтому в настоящее время многие усилия направлены на то, чтобы заставить раковые клетки перейти в апоптотическую стадию.…”
Section: результатыunclassified